Hubungan Kepatuhan Dan Keberhasilan Terapi Pada Pasien Tuberkulosis Paru Fase Intensif di Instalasi Rawat Jalan Balai Besar Kesehatan Paru Masyarakat Surakarta - Imamala, Betty; , Drs. Suharsono, Sp. FRS., Apt; , Arifah Sri Wahyuni, M.Sc., Apt (2016)
Tuberculosis is an infectious disease that need to be treated properly and in the long term. One of the therapeutic efficacy factor is medication adherence by patients. This study aims to determine the relationship of adherence to therapeutic efficacy in the Lung Health Center for Public Surakarta. Type of research is design observational with cross sectional analysis. This study was conducted in 100 adult patients with pulmonary tuberculosis outpatient BBKPM Surakarta who have received at least 3 months of therapy and control in February-March 2016, where samples were taken by purposive sampling technique. The tools used in this study is the MMAS-8 questionnaires and medical records. Correlation between scores adherence with the successful conversion were analyzed using Chi-square test. The results of the analysis obtained patient compliance by 94% adherent and non-adherent 6%. The therapeutic efficacy of the intensive phase therapy treatment successfully obtained 91% and 9% of therapy is not succesfull. there is a significant relationshipbetween medication adherence of patients with intensive phase of therapeutic efficacy in patients with pulmonary tuberculosis in the Lung Health Center for Public Surakarta with a contribution to the therapeutic efficacy of compliance of 2,84.